Perencanaan Pendidik dan Tenaga Kependidikan dalam Mentoring Adab di SDITA El Ma’mur Bogor - Suryati, Suryati; Tamam, Abas Mansur; Supraha, Wido (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The law of SISDIKNAS No.20 of 2003 article 52 paragraph 1 states that, “the management of Pre-school, Primary School, and Secondary School is carried out based on minimum standard service with the principle of school or madrasah based management.” The aims of this research is to analyze the management of educational staff and educators in Ma’mur Manaf As Salamah Foundation SDITA eL Ma’mur Bogor. The method that the researcher used is library research by taking references from books, journals, papers, articles, and newspapers that is relevant to this research. Data collection was carry out by in-depth interview, observation, and documentation studies. The result of this research found out that there are several steps in the management of human resources in this case educational staff and educators such as, (1) analyzing the condition and the availability of educational staff and educators, (2) designing and arranging the process of educational staff and educators recruitments’ program, (3) conduct observation and selection for the candidate of educational staff and educators, (4) the placement of human resources based on the requirement, (5) the coaching of human resource according to the qualification of each duty, (6) promotion and mutation, (7) dismissal, (8) compensation, and (9) the evaluation of the staff (reward and punishment (Arianto et al., 2019).